Knowledge of Malaria and Preventive Behaviour Amongst Allied Healthcare Workers at the Central African Republic - Alam, Urooj; Novera Sohail Bajwa; Rehana Khadim; Anam Haider; Ali Ghawas; Anam Manzoor (Pakistan Armed Forces medical journal, 2023)
Objective: to determine the knowledge of malaria and preventive behaviour among Allied Healthcare Workers at the Central African Republic. Study Design: Cross-sectional study. Place and Duration of Study: Central African Republic from Dec 2021 to May 2022. Methodology: Allied Healthcare Workers deployed at the Central African Republic as part of the International Organization for Peacekeeping were included in the study. A questionnaire was designed to determine the study participants’ knowledge and preventive behaviour. Association was made between the previous history of malaria and preventive behaviour using the chi-square test. Results: A total of two hundred and twenty-one (n=221) study participants were included in the study with a mean age of 35.73±4.89 years (Range: 22 to 47 years). 49(22.17%) Allied Healthcare Workers had a previous history of malaria. 212(95.9%) of the study participants had adequate knowledge about the mode of transmission and prevention practices. There was a significant association between the previous history of malaria and Allied Healthcare Workers’ preventive behaviour p<0.001). Conclusion: Most study participants had an adequate understanding of malaria, and those with prior malaria exhibited better preventive behaviour. In malaria-stricken regions, it is essential to take preventative measures.